Image Tracking and Volume Reconstruction of Medical Ultrasound - Arámbula-Cosío, Fernando; Fanti, Z; Torres, F; Lira, E; García-Segundo, C; Reyes-Ramírez, B; Hazan, E J; Gerson, R (Revista Mexicana de Ingenieria Biomedica, 2012)
In this work, the techniques available for real-time tracking of a clinical ultrasound probe are reviewed. Two methods of volume reconstruction, from tracked images, have been implemented, and their performance has been compared: a pixel-based method (PBM) and a voxel-based method (VBM). It is also presented the ultrasound probe calibration problem and the details of implementation of the crossed wire method of calibration, which produced accuracy and precision errors of calibration of 0.556 and 0.249 mm respectively. As a case study for 3D reconstruction, the reconstruction of a phantom of a breast with a tumor, is presented. Both methods (PBM and VBM) produced similar reconstructions with comparable computational performance.